What is colleagueship, actually? – A look at 25 years of research - Maarit Laiho; Arto Ryömä; Satu Teerikangas (United Kingdom, 2022)
Leadership is traditionally predominantly defined as a leader centered and individual activity. Role of colleagueship, the phenomenon of leadership among colleagues, who might hold relatively equal positions in an organizational hierarchy, remains underexplored in organization research. This paper diverges from prevailing leader driven approaches and emphasizes the role of each colleague at the workplace. The research question guiding our inquiry is What is known in previous literature on colleagueship at the workplace Our paper offers the preliminary findings from a systematic review of extant literature in management and organization research. Our findings indicate that whilst colleagueship itself is not researched, it is researched under the terms coworker or colleague. In addition, colleagueship appears to be indirectly researched as part of other organizational themes and as an implication in organizational life. The contribution of our paper is in recognizing an opportunity to introduce the concept of colleagueship into management and organization research.
BAM2019 Conference Proceedings